2022
DOI: 10.1055/s-0042-1748158
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccinations in Pregnancy: Comparative Evaluation of Acute Side Effects and Self-Reported Impact on Quality of Life between Pregnant and Nonpregnant Women in the United States

Abstract: Objective The objective of this study was to describe the acute side effects experienced by pregnant women who received a coronavirus disease 2019 (COVID-19) vaccine in the United States and to compare their experience to non-pregnant women of similar age. Study Design Adults who received a COVID-19 vaccine in the United States were invited via social media to enroll in an online, longitudinal, community-based registry (www.helpstopCOVID19.com). Participants self-reported pregnancy status, vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…There have been many studies that showed efficacy in preventing SARS-CoV-2 infection, hospitalization, and death due to COVID-19 including the Delta or Omicron VOC periods [ 14 , 15 , [23] , [24] , [25] ]. The favorable safety and efficacy of SARS-CoV-2 vaccines in pregnant women have also been reported [ [26] , [27] , [28] , [29] ] and SARS-CoV-2 vaccination in pregnant women at any stage of pregnancy has been recommended worldwide, including in Japan [ [30] , [31] , [32] ]. Our study results in the total cohort were consistent with previous reports and demonstrated the benefits of SARS-CoV-2 vaccination in pregnant women even in the Delta and Omicron VOC periods.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies that showed efficacy in preventing SARS-CoV-2 infection, hospitalization, and death due to COVID-19 including the Delta or Omicron VOC periods [ 14 , 15 , [23] , [24] , [25] ]. The favorable safety and efficacy of SARS-CoV-2 vaccines in pregnant women have also been reported [ [26] , [27] , [28] , [29] ] and SARS-CoV-2 vaccination in pregnant women at any stage of pregnancy has been recommended worldwide, including in Japan [ [30] , [31] , [32] ]. Our study results in the total cohort were consistent with previous reports and demonstrated the benefits of SARS-CoV-2 vaccination in pregnant women even in the Delta and Omicron VOC periods.…”
Section: Discussionmentioning
confidence: 99%
“…Rare side effects include thrombosis with thrombocytopenia syndrome, myocarditis, and pericarditis, Guillain–Barré syndrome, as in nonpregnant individuals; however, no infertility issues have been reported [ 78 , 79 , 80 , 81 ]. Pregnancy by itself does not represent a cause for increased risks of any adverse outcome, following COVID-19 vaccination [ 82 ], while the overall risk of the occurrence of an acute adverse event requiring medical attention is low (<1%) and similar in pregnant and unvaccinated pregnant patients [ 83 ]. Direct or indirect harmful effects on fertility, embryo/fetal development, pregnancy outcome, parturition, or short-term postnatal development of offspring were not detected [ 75 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…No harmful effects on fertility, embryo/fetal development, pregnancy outcome, parturition, or short-term postnatal development of offspring has been reported in association with vaccines. Side effects are similar in pregnant and non-pregnant females ( Brinkley et al, 2022 ).…”
Section: Vaccines and Pregnancymentioning
confidence: 93%
“…None of the recommended COVID-19 vaccines [Pfizer/BioNTech (Comirnaty) by Fosun Pharma, Pfizer; Moderna (Spikevax); Janssen/Johnson & Johnson by Janssen Pharmaceutical Companies] contain virus that replicates. Thus, they do not cause disease, but non-specific side-effects from activation of the immune system may occur ( Brinkley et al, 2022 ). Women can be assured that data supports the safety of vaccine in pregnancy and lactation.…”
Section: Vaccines and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation